2017
DOI: 10.1080/15592324.2017.1362518
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for external alkalinization in intact and in microwounded Chara cells are differentially sensitive to wortmannin

Abstract: Proton flows across the plant cell membranes play a major role in electrogenesis and regulation of photosynthesis and ion balance. The profiles of external pH along the illuminated internodal cells of characean algae consist of alternating high- and low-pH zones that are spatially coordinated with the distribution of photosynthetic activity of chloroplasts underlying these zones. The results based on confocal laser scanning fluorescence microscopy, pH microsensors, and pulse-amplitude-modulated chlorophyll mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…However, cells of Symbiodinium are also adapted to very low pH; recent studies have shown that the coral host acidifies the compartment (the "symbiosome") around endosymbionts to a pH of approximately 4, which provides the most photosynthetically accessible form of C i (CO 2 ) to Symbiodinium (29). Within PhenoChip, our expectation was thus that Symbiodinium cells exposed to pH < 6.0 would show increased carbon fixation and thereby increased effective quantum yields ( II ), as previously reported in filamentous green algae (30). Instead, in both strains, we found the highest  II to occur at pH 6.8.…”
Section: Discussionsupporting
confidence: 61%
“…However, cells of Symbiodinium are also adapted to very low pH; recent studies have shown that the coral host acidifies the compartment (the "symbiosome") around endosymbionts to a pH of approximately 4, which provides the most photosynthetically accessible form of C i (CO 2 ) to Symbiodinium (29). Within PhenoChip, our expectation was thus that Symbiodinium cells exposed to pH < 6.0 would show increased carbon fixation and thereby increased effective quantum yields ( II ), as previously reported in filamentous green algae (30). Instead, in both strains, we found the highest  II to occur at pH 6.8.…”
Section: Discussionsupporting
confidence: 61%
“…). Consistently, wortmannin also inhibits both pH banding and endocytosis in Chara , although to a lesser extend (Foissner et al , Bulychev and Foissner ). An argument against the hypothesis that continuous renewal of transporters is required to maintain ion transport is, that ikarugamycin, another inhibitor of endocytosis, has no effect on pH banding in Chara (own unpublished data).…”
Section: Discussionmentioning
confidence: 75%
“…In previous studies, we applied wortmannin, an inhibitor of PIP3 and PIP4 kinases which induces the formation of large aggregates consisting of TGN and MVBs (Foissner et al ). Wortmannin reduced the amplitude of pH peaks (Bulychev and Foissner ) but, in contrast to BFA, had only minor effects on long‐distance transmission of photometabolites (Bulychev and Foissner , own unpublished data). This may indicate that chloroplast‐released substances bind (preferentially) to the membrane of specific organelles.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations